2015
DOI: 10.1002/jsfa.7360
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in marine fish meat and consumer health: a review

Abstract: The numerous health benefits provided by fish consumption may be compromised by the presence of toxic metals and metalloids such as lead, cadmium, arsenic and mercury, which can have harmful effects on the human body if consumed in toxic quantities. The monitoring of metal concentrations in fish meat is therefore important to ensure compliance with food safety regulations and consequent consumer protection. The toxicity of these metals may be dependent on their chemical forms, which requires metal speciation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
213
0
22

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 495 publications
(263 citation statements)
references
References 117 publications
8
213
0
22
Order By: Relevance
“…Çevrede doğal olarak bulunan veya endüstriyel faaliyet nedeniyle oluşan metaller, poliklorlu bifeniller (PCB), dioksinler, diğer poliklorlu bileşikler bu canlıların bünyesinde birikebilir (Bosch, O'Neill, Sigge, Kerwath, & Hoffman, 2016). Belirli düzeyde organik cıva içeren bazı balık türlerinin fazla tüketiminin fetüs gelişiminde olumsuz etkilere neden olması gebelerde balık tüketiminin dezavantajı olarak değerlendirilebilir (; Dovydaitis, 2008).…”
Section: Gebelik Döneminde Balık Tüketimiunclassified
See 1 more Smart Citation
“…Çevrede doğal olarak bulunan veya endüstriyel faaliyet nedeniyle oluşan metaller, poliklorlu bifeniller (PCB), dioksinler, diğer poliklorlu bileşikler bu canlıların bünyesinde birikebilir (Bosch, O'Neill, Sigge, Kerwath, & Hoffman, 2016). Belirli düzeyde organik cıva içeren bazı balık türlerinin fazla tüketiminin fetüs gelişiminde olumsuz etkilere neden olması gebelerde balık tüketiminin dezavantajı olarak değerlendirilebilir (; Dovydaitis, 2008).…”
Section: Gebelik Döneminde Balık Tüketimiunclassified
“…Yüksek düzeyde histamin içeren bir balık taze gibi görünebilmektedir. Bu nedenle besin güvenliğini sağlamada balıkçılar, işletmeciler, dağıtıcı firmalara ve marketlere büyük görev düşmektedir (Visciano, Schirone, Tofalo, & Suzzi, 2012 (Bosch et al, 2016).…”
Section: Balık Tüketimi Yarar and Risk Analiziunclassified
“…In addition, pollution from anthropogenic activities is an important means of releasing Al into the marine environment. However, Al accumulation in fish, marine plants and other organism depends on several factors such as the species, age, sex, etc [60,61]. Several studies have reported that the aluminium polymerization from aqueous aluminium, which takes place in a pH of between 5.0 and 6.0, which leads to acute toxicity in fish because it causes damage to the functioning of fish gills resulting in respiratory and ion regulatory dysfunctions [62,63].…”
Section: Animal Productsmentioning
confidence: 99%
“…Among various problems, the release of toxic heavy metals-such as lead (Pb), arsenic (As), or cadmium (Cd)-into the river or sea has been considered a worldwide issue due to their non-biodegradability and accumulation, threatening the aquatic life and human health [6][7][8][9]. Particularly, water pollution by arsenic presents severe problems for human health, including skin damage and cancer due to its good mobility in water-especially in India, Bangladesh, and Vietnam [6,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%